2020
DOI: 10.1161/jaha.120.017316
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Bleeding in the Perioperative Anticoagulant Use for Surgery Evaluation Study

Abstract: Background In the PAUSE (Perioperative Anticoagulant Use for Surgery Evaluation) Study, a simple, standardized, perioperative interruption strategy was provided for patients with nonvalvular atrial fibrillation taking direct oral anticoagulants (DOACs). Our objective was to define the factors associated with perioperative bleeding. Methods and Results We analyzed bleeding as the composite of major and clinically relevant nonmajor bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 27 publications
0
33
1
Order By: Relevance
“…The results of our study are in contrast to the results of the PAUSE study, which demonstrated that the use of a standardized protocol to stop DOAC treatment before elective procedures resulted in residual DOAC levels below 30 ng/mL in more than 67% of patients and less than 5.3% were above 50 ng/mL. 24 In contrast, the wide range and high levels of DOAC concentrations observed in our registry are due to the life-threatening clinical situations in which the anticoagulants cannot be stopped in time. In these critical situations rapid and quantitative determination of DOAC concentrations seems to be essential to estimate the bleeding risk in these special patient populations.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of our study are in contrast to the results of the PAUSE study, which demonstrated that the use of a standardized protocol to stop DOAC treatment before elective procedures resulted in residual DOAC levels below 30 ng/mL in more than 67% of patients and less than 5.3% were above 50 ng/mL. 24 In contrast, the wide range and high levels of DOAC concentrations observed in our registry are due to the life-threatening clinical situations in which the anticoagulants cannot be stopped in time. In these critical situations rapid and quantitative determination of DOAC concentrations seems to be essential to estimate the bleeding risk in these special patient populations.…”
Section: Discussioncontrasting
confidence: 99%
“… 27 , 67 In this study, hypertension was the only modifiable risk factor in predicting bleeding events. 67 …”
Section: Available Data On Specific Antithrombotics and Oculoplastic ...mentioning
confidence: 72%
“…A sub-analysis of patients in the PAUSE trial found that separating patients into residual levels of > 50 ng/mL or £ 50 ng/ mL did not result in significant association with major and nonmajor bleeding events, suggesting that checking residual drug levels prior to surgery does not help to predict bleeding events when drugs are stopped at the times used in the study 1800 .…”
Section: -When Should Chronic Anticoagulation Be Stopped In Patients ...mentioning
confidence: 99%
“…Oberweis et al, reported that procedure type (Spinal surgery > THA > TKA), active cancer, female sex, CAD and chronic obstructive pulmonary disease (COPD) are independent risk factors for MBE 634 . Previous perioperative bleeding and active cancer are known as risk factors for MBE after surgical procedures 635,636 In a recent study, Tafur et al, found that hypertension is also a risk factor for perioperative bleeding 637 . In a systematic review performed by Borre et al, in a patient group with 322,010 patients, patients with chronic kidney disease are at increased risk for MBE (moderate strength of evidence) 638 .…”
Section: - Is There a Role For Stratification Of Patients Undergoing ...mentioning
confidence: 99%